(untitled) (Scientific journal of the Fergana State University, 2023)
The article emphasizes that the issues of legal regulation of youth state policy are addressed in the political processes on important aspects of its development and implementation, as well as mechanisms of organizational management. In particular, the chronological stages of the process of formation and implementation of the state youth policy in the country were discussed.